The use of two mating systems in breeding for resistance to Maruca testulalis Gey. in cowpea Vigna unguiculata (L.) Walp - Woolley, Jonathan N.; Evans, AM (Cambridge University Press, 1984)
Resistance to insects in cow peas was studied in a diallel cross and in a test cross. Number of pods and seed yield under unsprayed conditions, expressed as a percentage of their values under sprayed conditions, were confirmed as reliable characters for the assessment of resistance and as suitable for diallel analysis. Non-allelic interaction was not detected for these ratios despite its presence in yields. Resistance to flower damage by Maruca and resistance to all damage by post-flowering pests were both highly heritable and were controlled polygenically by alleles showing partial dominance. The test cross was not as informative as the diallel cross in the analysis of the genetic control of resistance in a group of moderately resistant lines, but was useful in selecting the best of these for future crosses. The results from both schemes suggested that resistance should be accumulated by intercrossing resistant lines before attempting to transfer it to agronomically-preferred susceptible lines.